Anomalous origin of the vertebral artery - Dodevski, Ace; Lazareska, Menka; Aliji, Vjolca; Zafirova, Biljana; Trpkovska, Biljana (Macedonian Association of Anatomists and Morphologists, 2010)
The posterior circulation of the brain consists of the vertebrobasilar system and its branches. Vertebral arteries are responsible for about 30% of brain blood supply. The aim of this study was to examine the origin of the vertebral artery and to present the anatomic variations of the vertebral artery origin as well as the percentage of their appearance in the population. Material and methods: The origin of the vertebral artery was investigated in 30 patients; a total of 60 vertebral arteries were examined with CT angiography and DSA by Seldinger technique. Results: Abnormal origin of the vertebral artery was found in one (3.3%) patient. Vertebral artery originated directly from the aortic arch, as a second branch between left subclavian artery and left common carotid artery. Conclusion: Real abnormality of the origin of the vertebral artery is rare; in our series it was found in 3.3% of the cases. The described variations of the vertebral artery origin are not only interesting from the anatomical point of view, but they also find clinical applications in the surgery and diagnostic and therapeutic radiology.
Варијации во потеклото на 'рбетната артерија
Keywords: vertebral artery; origin; anatomy; angiography; computed tomography